DramAcum – The New Wave of Romanian contemporary dramaturgy - Dominte, Carmen (Swedish Journal of Romanian Studies, 2019)
During the nineties, a new theatrical trend developed. It was called New European Drama or New Writing. It was represented by authors such as the British Sarah Kane, Mark Ravenhill or the German playwright Marius von Mayernburg. The classical theatre will never be able to return to itself, unless giving the spectator the utopian sense of life that only a staged play could perform, not from a delusive perspective, but from a real and personalized perspective, giving a certain meaning to reality. Being against the conservatory type, the authors put an end to all the theatrical conventions. They considered that it had to come to a point of changing the old patterns, of introducing new themes, new structures, new means of performing in the attempt of seducing and shocking the audience. Most of the dramatic texts focus on the plots about hard human existence such as racism, madness, suicide, sexuality, drug addiction and any type of abuse. The language is vulgar and slangy. All the dramatic texts when performed on stage invade the personal space of the people watching, who is now considered one of the characters. It is not only the dramatic text that is taken into consideration, but the performance itself. The new type of theatre developed in Russia, Poland and Romania, giving specific projects (Teatr.doc, The Drama Laboratory and DramAcum). All were influenced by the verbatim dramatic style performed in theatres under the slogan of the in-yer-face. The study intends to explore the importance of the Romanian theatrical project – DramAcum, as a new type of theatre and dramaturgy.